Syrian Refugees in Turkey Between Reception and Integration - Şahin-Mencütek, Zeynep (IMISCOE Research Series, 2023)
This open access book provides a comprehensive analysis of Turkey's response to Syrian mass migration from 2011 to 2020. It examines internal and external dimensions of the refugee issue in relation to Middle Eastern geopolitics as well as the salience of controlling irregular migration to the European Union. The book focuses on policies and discourses developed in the fields of border management, reception, asylum and protection, and integration of refugees with an emphasis on continuities, ruptures and changes. One of its main goals is to compare differences in policy practices across provinces in order to better capture ways in which Syrian refugees claim agency, develop belonging and experience integration in the context of cultural intimacy, precarity and temporariness. By providing rich empirical evidence, this book provides a valuable resource for students and scholars in migration studies, political science, anthropology, sociology and public administration disciplines as well as policy makers, stakeholders and the general public.